Cabin Fever Syndrome Post-SARS-CoV-2: Design and Validation of a Scale - Corrales, Angela Cristina Yánez; Yánez, Erika; Pozo, Juan Pablo; Monga, Rafael; Santy, Lucía Flores (Journal of Ecohumanism, 2025)
Objective: The primary objective of this research is to design and validate an instrument called "CSC-19" to assess Cabin Fever Syndrome in health students and professionals. Methodology: A descriptive cross-sectional design was used. 499 health students and teachers participated in this study. The internal consistency and linguistic validation of the instrument were evaluated. Cronbach’s alpha was used to analyze the reliability of the instrument, and the Pearson statistical test was used to establish the correlation between the elements of the form. Results and Discussion: The correlation of the instrument was analyzed, according to Pearson’s correlation statistic, obtaining an average of 0.521 between the 25 elements; 22 of which presented a high correlation. Regarding the reliability of the instrument, significant results were obtained in the parameters Risk of outings (0.964), return to normality (0.963), avoidability (0.965), risk thinking (0.963), preventive activities (0.965), emotions (0.963) and beliefs (0.967). Conclusions: The proposed instrument can support future research to apply it in educational environments of health training in the effects of social isolation, being able to identify parameters of mental health impairment in both university students and health professionals in their teaching work.